Pharmacoeconomic analysis of antithrombotic therapy in patients with acute coronary syndrome and patients with atrial fibrillation who underwent percutaneous coronary intervention - V. А. Ryagina; К. I. Matrenin; D. G. Shchurov; Т. S. Teptsova (IRBIS LLC, 2023)
Objective: to assess the clinical and economic feasibility of ticagrelor in combination with acetylsalicylic acid (ASA) in comparison with clopidogrel in combination with ASA in patients with acute coronary syndrome (ACS), including both those who underwent, and those who did not undergo percutaneous coronary intervention (PCI) or coronary artery bypass grafting (CABG); and new oral anticoagulants (NOACs) in combination with clopidogrel in comparison with warfarin in combination with clopidogrel and ASA in patients with atrial fibrillation (AF) who underwent PCI; to identify the impact of the above strategies of antithrombotic therapy on the targets of the State Health Care Program of the Russian Federation (RF) "Development of Health Care" and the Federal Project "Cardiovascular Diseases Control".Material and methods. The clinical and economic study (CES) of ticagrelor in combination with ASA in ACS patients was based on a costbenefit analysis. A combined model, including a decision tree and Markov model was developed. The horizon period of the analysis was 5 years. Quality-adjusted life year (QALY) was used as an efficiency criterion and only the direct medical costs associated with the conditions identified in the modeling were taken into account. A discount rate of 5% was taken into account during the CES. The application of NOACs in combination with clopidogrel was studied in the CES using a cost minimization analysis considering the costs per patient characterized by the presence of AF regardless of the presence of ACS and a history of PCI.Results. We used a decision tree and Markov modeling in adult patients with ACS, who had or had not undergone PCI or CABG, in the horizon period of 5 years considering the discount rate of the added quality-adjusted life year (incremental cost-effectiveness ratio (ICER) per QALY). The result for ticagrelor in combination with ASA compared to clopidogrel in combination with ASA was 605,199 rubles, which was significantly lower than the willingness-to-pay threshold (2,235,201 rubles). Assessment of the impact of the therapy regimen including ticagrelor in combination with ASA on the target indicators of the State Health Care Program of the RF "Development of Healthcare" and the Federal Project "Cardiovascular Diseases Control" showed that the use of this therapy regimen will reduce mortality from myocardial infarction (MI) and cardiovascular causes by 2.45 cases per 100 thousand population provided that 100% of patients with MI and unstable angina in the RF are transferred from clopidogrel + ASA scheme to ticagrelor + ASA. The potential contribution of ticagrelor in combination with ASA compared to clopidogrel in combination with ASA in patients with ACS in achieving the target reduction of mortality from circulatory diseases will be 6.48% by 2023. In all simulated scenarios, in the group of patients with AF who had undergone PCI, pharmacotherapy regimens containing NOACs (dabigatran etexilate, rivaroxaban, apixaban) were more costly than therapy regimens containing warfarin (with not significantly different effectiveness).Conclusion. The results of the evaluation of clinical and economic feasibility of antiplatelet therapy strategies demonstrated the costeffectiveness of ticagrelor in combination with ASA compared to clopidogrel in combination with ASA in patients with ACS, including those who had undergone PCI or CABG and those who had not. The strategy of ticagrelor + ASA showed a favorable effect on the rates of mortality from MI, as well as from circulatory diseases. The results of the clinical and economic evaluation of the four strategies of antithrombotic drug therapy in patients with AF who had undergone PCI showed higher costs of the regimens containing NOACs with a presumed zero effect on the mortality from circulatory diseases.